Farmers Motivation in Dairy Goats Exertionat the Slope Area of Merapi Volcano - Haryadi, F. Trisakti (2015)
The objective of the study was to analyze farmers motivation including some motives that encouraged the farmers to raise dairy goats in the slope area of Merapi Volcano. Sixty dairy goat farmers at Turgo Sub-village were randomly selected as respondents. Data were collected by interviewing directly to the respondents using a good prepared questionnaire that was tested its validity and reliability. Descriptive analysis was used to describe the motives of the farmers. The results showed that there were a high level of motives including use of land motives (81.6%), economics motives (76.7%), and use of family labor motives (83.4%). But, most of the farmers (56.6%) were in medium level for safety motives